Integrated Analysis of Transcriptome and Metabolome Reveals the Mechanism of Chlorine Dioxide Repressed Potato (Solanum tuberosum L.) Tuber Sprouting - Zheng, Xiaoyuan; Li, Mei; Tian, Shilong; Li, Shouqiang; Chen, Jianxin; Zhang, Xuejiao; Wu, Xiaohua; Ge, Xia; Tian, Jiachun; Mu, Yuwen; Song, Juan (Frontiers in Plant Science, 2022)
Sprout is an irreversible deterioration of potato quality, which not only makes potatoes lose their commercial value but also produces harmful toxins. As an internationally recognized disinfectant, chlorine dioxide can inhibit the sprout of potato tubers. However, there is no report on the mechanism of chlorine dioxide inhibiting potato germination by transcriptome and metabolomics. In this study, the transcriptome and metabolome of potatoes treated with chlorine dioxide (ClO2) were sequenced and the results showed that 3119 differential genes were screened after ClO2 treatment. 1872 genes were up-regulated and 1247 genes were down-regulated. The up-regulated differential genes are mainly concentrated in phenylpropanoid biosynthesis, MAPK signaling pathway-plant, and the down-regulated genes are mainly concentrated in plant hormone signal transduction. The metabonomic sequencing found a total of 932 metabolites, of which 52 were up-regulated and 33 were down-regulated. The up-regulated metabolites are mainly flavonoids and coumarins, and the down-regulated metabolites are mainly alkaloids and amino acid and derivatives. Integrated analysis of transcriptomics and metabolomics results showed that a variety of different metabolites were regulated by a variety of different genes, forming a complex regulatory network. The above results provide new insights for ClO2 to inhibit potato sprout.